Integrating biomarkers and multi-parametric MRI to provide enhanced clinical diagnosis for prostate cancer - Alter, Jason; Albala, David M. (Frontiers in Urology, 2023)
Prostate cancer (PCa) risk assessment can incorporate clinical features, gene expression, protein ‘biomarkers’ or imaging. In this review the benefits of layering multiparametric magnetic resonance imaging (mpMRI) with other risk assessment methods is considered. mpMRI is an increasingly utilized risk assessment tool in prostate cancer. The European Association of Urology, National Comprehensive Cancer Network (NCCN) and American Urological Association (AUA) guidelines call for mpMRI utilization in the prostate cancer management pathway. As such, the NCCN Guidelines and AUA guidelines emphasize differing levels of reliance on mpMRI preceding prostate biopsy. However, like all risk assessment tools, mpMRI has strengths and limitations. This include dependencies on reader expertise and interpretation, equipment and process standardization, tumor size, tumor multifocality, tissue architecture, ethnic and racial disparity, and cost. Thus, layering complementary risk assessment methods to mitigate the limitations of each approach, enables the most informed clinical management. The goal of ongoing biomarker/mpMRI studies is to provide insight into the clinically helpful integration of the two approaches. For new technologies to be adapted or layered together synergistically, five specific competencies must be considered acceptable: (1) efficacy, (2) potential side effect levels, (3) ease of use of technology, (4) cost vs. clinical benefit, and (5) durability.